Imunidade tributária e os livros eletrônicos - Lopes, Priscila Silva (2013)
The purpose of this study is to explore de possibility to apply the tax immunity conveyed in art. 150, VI, d, of the Federal Constitution, to electronic books. In order to accomplish this, first, considerations about the power limitations of taxing were explored. Second, the research studied the scope attributed to the word book set in such a device framework. Based on this study, this work evaluated the possibility of invoking the tax immunity to electronic books the same way as the books printed on paper